Denmark : Financial System Stability Assessment, including Reports on Observance of Standards and Codes on the following topics, Banking Supervision, Insurance Supervision, Systematically Important Payment. (IMF Staff Country Reports; Country Report ;, 2006)
The Financial System Stability Assessment of Denmark has been developed to identify the weakness in the financial sector structure and thereby enhance the resilience to macroeconomic shocks and cross-border contagion. This paper provides the overall stability assessment of the financial system and the autonomy and accountability of the Danish Financial Supervisory Authority (DFSA). It reviews the macroeconomic setting, financial structure and risks. The study also analyzes the financial markets, their structure and safety nets, and assesses financial supervision, standard assessments, and key recommendations to improve the Anti-Money Laundering and Combating the Financing of Terrorism (AML-CLT) system.